Sosialisasi Pemanfaatan Energi Matahari Pada Pendingin Kapal Ikan di Nelayan Blimbing, Paciran, Lamongan, Jawa Timur. - Sugianto, Erik; Suryadhi, Suryadhi; Prasutiyon, Hadi; Wicaksana Shakti, M. Duta (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
In the coastal areas of East Java, especially in the Blimbing area, Paciran District, Lamongan Regency, most of the population works as fishermen who catch marine fish. One of the problems faced by fishermen is the use of ice cubes to preserve fish. However, ice cubes can reduce fish quality, melt easily, and are expensive. Also, it adds to the burden of the ship and increases the consumption of fuel oil (BBM). This socialisation programme aims to overcome these problems by introducing a cooling system that uses renewable energy through solar energy. This activity was carried out by presenting material and designing a solar cooling system on the boat. With this system, fishermen are expected to maintain good fish quality, increase production, and reduce operational costs, especially for fuel and ice, thereby increasing fishermen's income. This solar energy cooling system produces 1050 WP of power per day and has a battery capacity of 2400 Wh, and the ability to cool the freezer for an average of 12 hours per day.